استخدام المؤشرات البيوكيميائية طرائق فعالة في الكشف عن التباين الوراثي ضمن أصناف القمح السداسية والرباعية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
استخدمت تقنيتا  A-PAGE , و SDS-PAGE , لوصف 38 صنفاً, من القمح القاسي, و12 صنفاً, من القمح الطري. نتج من التقانة الأولى 13 حزمة متباينة, ومن الثانية 12 حزمة, متباينة, مرتفعة الوزن الجزيئي(glutenin subunits  high molecular wheight) (HMW-GS). جمعت البيانات كاملة (25 حزمة متباينة), وحُسب معامل التشابه الوراثي, بين الأصناف المدروسة, بحسب (Jaccard (1908. ثم أُدرج, بعد ذلك, مخطط التحليل العنقودي, مظهراً القرابات الوراثية بين الأصناف المدروسة, بحسب طريقة (UPGMA). بلغت نسبة التنوع الوراثي ضمن الأصناف القاسية 56%, أما في القمح الطري فبلغت 100%. أظهرت شجرة القرابة, التي ضمت الأصناف الطرية, والقاسية, انفصال أصناف الطرية, في عنقود مستقل, عن الأصناف القاسية. يُستنتج, من هذه الدراسة, فعالية بروتينات التخزين (جليادين وجلوتينين), بوصفها مؤشراً مفيداً, للكشف عن التباينات الوراثية, ضمن أصناف القمح, ودراسات التنوع الوراثي, وتسجيل أصناف جديدة, واختبارات النسب. In this study two techniques (A-PAGE&SDS-PAGE) have been applied to characterize 38 durum wheat varieties and 12 bread wheat varieties. Number of bands resulted by applying the first metohd (A-PAGE) was 13 polymorphic bands, while 12 HMW- GS (high molecular wheigt glutenin subunits) have been resulted by applying SDS-PAGE. Data were combined together (25 polymorphic bands) to calculate the genetic similarities between studied individuals using Jaccard's coeficient followed by setting up the cluster analysis using UPGMA method. The value of genetic diversity was 56% between durum wheat varieties, while the same value was increased to reach 100% in the bread wheat varieties. Dendogram for all 50 genotypes  showed a separation of  bread  wheat varieties in a sub cluster which is distinct from the sub cluster containig the bread wheat varieties. Finally we could conclude the effectivness of  seed storage protein marker as a useful tools to characterize individuals, evaluate genetic diversity, registration of new varieties and pedigree analysis studies.